Molecular diversity based heterotic groups in pigeonpea [Cajanus cajan (L.) Millsp.] - Mudaraddi, Bharathi; Saxena, K.B. (The Indian Journal of Genetics and Plant Breeding, 2016)
A set of 155 hybrid parents was characterized at molecular level using 24 simple sequence repeat (SSR) markers.The number of alleles amplified ranged from 3 to 41 at an average of 14.5 alleles per marker and mean polymorphic information content (PIC) value of 0.64.Based on genetic diversity,three heterotic groups were constituted. Male sterile (A) lines were distributed into two heterotic groups, while the fertility restorer (R) lines formed three heterotic groups. Of the 135 restorers studied, 51 (37.78%) were classified in heterotic group I, and 75 (55.56%) in heterotic group II. Six interspecific derivatives and three other genotypes constituted the heterotic group III. These observations indicated the presence of limited genetic diversity among A and R lines. Based on the present results, it is recommended that for breeding high yielding pigeonpea hybrids, more attention be given to develop new genetically diverse hybrid parents.